2008
DOI: 10.1523/jneurosci.5749-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of GluR1-Containing AMPA Receptors to a Spinal Nociceptive Synapse during Acute Noxious Stimulation

Abstract: /calmodulindependent protein kinase II (CaMKII)-dependent pathway, has been proposed to underlie certain forms of hyperalgesia, the enhanced pain sensitivity that may accompany inflammation or tissue injury. However, the specific synaptic populations that may be subject to such plasticity have not been identified. Using neuronal tracing and postembedding immunogold labeling, we show that a model of acute inflammatory hyperalgesia is associated with an elevated density of GluR1-containing AMPA receptors, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 45 publications
5
76
0
Order By: Relevance
“…Blocking or deletion of AMPA receptor subunits therefore reduces glutamate-dependent signaling and alleviates hyperalgesia and allodynia in rodent models of inflammatory or neuropathic pain (Garry et al, 2003;Larsson and Broman, 2008;Luo et al, 2008). Synaptic plasticity at glutamatergic synapses is mediated by changes in the surface expression of AMPA receptors (Fig.…”
Section: Receptor Trafficking and Synaptic Vesicle Exocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking or deletion of AMPA receptor subunits therefore reduces glutamate-dependent signaling and alleviates hyperalgesia and allodynia in rodent models of inflammatory or neuropathic pain (Garry et al, 2003;Larsson and Broman, 2008;Luo et al, 2008). Synaptic plasticity at glutamatergic synapses is mediated by changes in the surface expression of AMPA receptors (Fig.…”
Section: Receptor Trafficking and Synaptic Vesicle Exocytosismentioning
confidence: 99%
“…NMDA receptor-mediated activation of nNOS resulted in increased S-nitrosylation of stargazin (Figs. 3, 5, and 6) and, subsequently, increased binding and surface expression of the AMPA receptor subunit GluR1 (Selvakumar et al, 2009) suggesting a nitric-oxide-dependent feed-forward activation that may contribute to the development of hyperalgesia. Inflammatory hyperalgesia is associated with an increase of the membrane density of GluR1-containing AMPA receptors in nociceptive neurons of the dorsal horn of the spinal cord and a relative decrease of GluR2/3 subunits (Larsson and Broman, 2008). Deletion models revealed that a lack of GluR2 intensifies long-term potentiation upon tetanic stimulation (Jia et al, 1996;Youn et al, 2008).…”
Section: Receptor Trafficking and Synaptic Vesicle Exocytosismentioning
confidence: 99%
“…Acute inflammatory pain is associated with increased insertion of GluA1-containing AMPARs in the spinal dorsal horn (Galan et al, 2004;Larsson and Broman, 2008), and GluA2 internalization mediated by protein kinase C (PKC) activation is associated with persistent inflammatory pain (Park et al, 2009). In addition, stimulation of N-methyl-D-aspartate receptors (NMDARs) can induce GluA2 internalization in the hippocampus and hypothalamus (Tigaret et al, 2006;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…AMPARs are ionotropic glutamate receptors and form heterotetramers, comprised of a combination of four subunits (GluR1-GluR4) (9,10). A number of studies demonstrated that synaptic insertion of GluR1-containing AMPARs contributes to the synaptic potentiation during LTP and experience-dependent neuronal plasticity (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%